The Ethnic Origin of the Nusayris (Journal of Alevism-Bektashism Studies, 2023)
The Nusayris (Arab Alevis), who live in Hatay, Adana, and Mersin, have a more isolated and secretive organization than other ethnic groups. They are known and recognized as “Fellah” and “Arab Uşağı” among the people. The term “Nusayri” is not commonly used among the general public, but only in scientific literature. They have continued their secrecy and closed community life, which they see as a way to protect their traditions and beliefs and to sustain their lives, as a completely protective and defensive mechanism until today. Nusayrism is a batini Islamic sect based on the deification of Ali, the strength of the belief in Khidr, the strength of the belief in the tomb, the belief in transmigration, the belief that all religions, all prophets, and even those who produce knowledge are sacred, and the closed community organization and secrecy. All of these characteristics, which are functionally interconnected, constitute the Nusayri belief system. In Hatay, the most populous ethnic group in terms of population is Turkish Sunnis. Nusayris (Arab Alevis) constitute the second largest ethnic group in terms of population. Arab Sunnis and Arab Christians are also a significant number in terms of population. The mother tongue of Turkish Sunnis is Turkish. The mother tongue of Arab Alevi, Arab Sunni, and Arab Christian outside of this group is Arabic, but they also use Turkish as a spoken language. They are known and recognized as “Fellah” and “Arab Uşağı” among the people. “Fellah” means farmer in Arabic. The reason for being called Fellah is that these people have been farming for centuries by working as laborers or associates alongside large landowners. “Arab Uşağı” means emphasizing their Arab ethnic origin, and the word “Nusayri” is not known to the people, but is only used in scientific literature. Although many sources provide brief information about the history of the Nusayris, most of them are also inconsistent information. There is uncertainty about their ethnic origin, as well as about the history of the Nusayris. In this study, the ethnic identity of the Nusayris living in Hatay will be discussed and explained based on the sources studied and the findings obtained from the field.